PET imaging approaches for inflammatory lung diseases: Current concepts and future directions. Issue 86 (January 2017) - Chen, Delphine L.; Schiebler, Mark L.; Goo, Jin Mo; van Beek, Edwin J.R.
Highlights: Positron emission tomography can provide molecular information inflammatory lung disease mechanisms and assess targeted treatment responses. 18 F-Fluorodeoxyglucose, 18 F-(+/−)NOS, and 18 F-fluciclatide have potential for serving as biomarkers of inflammation and fibrosis. PET can complement computed tomography and magnetic resonance imaging to improve our understanding of inflammatory lung disease mechanisms. Abstract: Inflammatory lung disease is one of the most common clinical scenarios, and yet, it is often poorly understood. Inflammatory lung disorders, such as chronic obstructive pulmonary diseases, which are causing significant mortality and morbidity, have limited therapeutic options. Recently, new treatments have become available for pulmonary fibrosis. This review article will describe the new insights that are starting to be gained from positron emission tomography (PET) methods, by targeting molecular processes using dedicated radiotracers. Ultimately, this should aid in deriving better pathophysiological classification of these disorders, which will ultimately result in better evaluation of novel therapies.